Analysis of a National Programme for Selective Internal Radiation Therapy for Colorectal Cancer Liver Metastases. Issue 1 (January 2019) - White, J.; Carolan-Rees, G.; Dale, M.; Morgan, H.E.; Patrick, H.E.; See, T.C.; Beeton, E.L.; Swinson, D.E.B.; Bell, J.K.; Manas, D.M.; Crellin, A.; Slevin, N.J.; et al.
Abstract: Aims: Patients with chemotherapy-refractory colorectal cancer liver metastases have limited therapeutic options. Selective internal radiation therapy (SIRT) delivers yttrium 90 microspheres as a minimally invasive procedure. This prospective, single-arm, observational, service-evaluation study was part of National Health Service England Commissioning through Evaluation. Methods: Patients eligible for treatment had histologically confirmed carcinoma with liver-only/liver-dominant metastases with clinical progression during or following oxaliplatin-based and irinotecan-based chemotherapy. All patients received SIRT plus standard of care. The primary outcome was overall survival; secondary outcomes included safety, progression-free survival (PFS) and liver-specific PFS (LPFS). Results: Between December 2013 and March 2017, 399 patients were treated in 10 centres with a median follow-up of 14.3 months (95% confidence interval 9.2–19.4). The median overall survival was 7.6 months (95% confidence interval 6.9–8.3). The median PFS and LPFS were 3.0 months (95% confidence interval 2.8–3.1) and 3.7 months (95% confidence interval 3.2–4.3), respectively. During the follow-up period, 143 patients experienced an adverse event and 8% of the events were grade 3. Conclusion: Survival estimates from this pragmatic study show clinical outcomes attainable in the National Health Service comparable with previously published data. This study shows the value of a registry-based commissioning model to aid national commissioning decisions for highly specialist cancer treatments.